Study Behaviors and USMLE Step 1 Performance: Implications of a Student Self-Directed Parallel Curriculum. (November 2017) - Burk-Rafel, Jesse; Santen, Sally A.; Purkiss, Joel
Abstract : Purpose: To determine medical students' study behaviors when preparing for the United States Medical Licensing Examination (USMLE) Step 1, and how these behaviors are associated with Step 1 scores when controlling for likely covariates. Method: The authors distributed a study-behaviors survey in 2014 and 2015 at their institution to two cohorts of medical students who had recently taken Step 1. Demographic and academic data were linked to responses. Descriptive statistics, bivariate correlations, and multiple linear regression analyses were performed. Results: Of 332 medical students, 274 (82.5%) participated. Most students (n = 211; 77.0%) began studying for Step 1 during their preclinical curriculum, increasing their intensity during a protected study period during which they averaged 11.0 hours studying per day (standard deviation [SD] 2.1) over a period of 35.3 days (SD 6.2). Students used numerous third-party resources, including reading an exam-specific 700-page review book on average 2.1 times (SD 0.8) and completing an average of 3, 597 practice multiple-choice questions (SD 1, 611). Initiating study prior to the designated study period, increased review book usage, and attempting more practice questions were all associated with higher Step 1 scores, even when controlling for Medical College Admission Test scores, preclinical exam performance, and self-identified score goal (adjusted R 2 = 0.56, P < .001). Conclusions: Medical students at one public institution engaged in a self-directed, "parallel" Step 1 curriculum using third-party study resources. Several study behaviors were associated with improved USMLE Step 1 performance, informing both institutional- and student-directed preparation for this high-stakes exam. Abstract : Supplemental Digital Content is available in the text.